The prognostic significance of further axillary dissection for sentinel lymph node micrometastases in female breast cancer: A competing risk analysis using the SEER database - Zhou, Yudong; Pu, Shengyu; Jiang, Siyuan; Li, Danni; Li, Shouyu; Liu, Yang; Ren, Yu; Hao, Na (Frontiers in Oncology, 2022)
BACKGROUND: Sentinel lymph node (SLN) biopsy has been widely recognized as an excellent surgical and staging procedure for early-stage breast cancer, and its development has greatly improved the detection of micrometastases. However, the axillary treatment of micrometastasis has been the subject of much debate. METHODS: We identified 427,131 women diagnosed with breast cancer from 2010 to 2018 in the Surveillance, Epidemiology, and End Results (SEER) database. Patients whose nodal status was micrometastases (pTxN1miM0) were classified into two groups: the SLNB only group and SLNB with complete ALND group, and we used these classifications to carry out propensity-score matching (PSM) analysis. The primary and secondary endpoints were OS and BCSS, respectively. We then implemented the Kaplan-Meier method and Cox proportional hazard model and used Fine and Gray competitive risk regression to identify factors associated with the risk of all-cause mortality. RESULTS: After the PSM, 1,833 pairs were included in total. The SLNB with complete ALND showed no significant difference in OS (HR=1.04, 95% CI: 0.84-1.28, P=0.73) or BCSS (HR= 1.03, 95% CI: 0.79-1.35, P=0.82) compared to the SLNB only group, and axillary treatment was not associated with breast cancer-specific death (BCSD) (HR=1.13, 95% CI: 0.86-1.48, P=0.400) or other cause-specific death (OCSD) (HR=0.98, 95% CI:0.70-1.38, P=0.920). There was no statistically significant difference in the cumulative incidence of BCSD (Grey’s test, P=0.819) or OCSD (Grey’s test, P=0.788) for between the two groups either. For different molecular subtypes, patients in the SLNB only group showed no statistically significant differences from those in the SLNB with complete ALND group with Luminal A (HR=1.00, 95% CI:0.76-1.32, P=0.98) or Luminal B (HR=0.82, 95% CI:0.42-1.62, P=0.55) but similar OS to HER2-enriched (HR=1.58, 95% CI:0.81-3.07, P=0.19) or triple negative breast cancers (HR=1.18, 95% CI:0.76-1.81, P=0.46). CONCLUSIONS: Our results suggest that in early breast cancer patients with micrometastasis, complete ALND does not seem to be required and that SLNB suffices to control locoregional and distant disease, with no significant adverse effects on survival compared to complete ALND.